Lymph node micrometastases are associated with disease recurrence and poor survival for early-stage non-small cell lung cancer patients: a meta-analysis. Issue 1 (December 2016) - Deng, Xu; Jiang, Li; Liu, Quan; Zhou, Dong; Hou, Bing; Cui, Kefan; Min, Jia; Dai, Ji
Abstract Background We performed a meta-analysis to clarify whether the molecular detection of tumor cells or micrometastases in the lymph node (LN) indicates a high risk of disease recurrence and poor survival in negative pathologic lymph node status non-small cell lung cancer (NSCLC). Methods A literature search was performed using relevant keywords. We searched relevant studies from PubMed, Embase, and the Cochrane Library. Direct and indirect meta-estimates were generated using Review Manager software with fixed effects for the study. Study-to-study heterogeneity was summarized usingI 2 statistics and predictive intervals (PIs). Results Our analysis of eight eligible studies revealed that patients with lymph node micrometastases (LNMM) were associated with poor overall survival (OS) (HR, 1.98; 95 % CI, 1.50 to 2.62;p < 0.00001) and disease-free survival (DFS) (HR, 2.34; 95 % CI, 1.67-3.27;p < 0.00001). Conclusion LNMM is associated with an increased risk of disease recurrence and poor survival in patients with negative pathologic node negative NSCLC. Thus, these patients need to be carefully followed up after the initial pulmonary resection.